Search 83,320 tutors
FIND TUTORS
Ask a question
0 0

Solve for x. –3(x + 1) = 2(x – 8) + 3

Tutors, please sign in to answer this question.

2 Answers

-3(x+1) = 2(x-8) + 3
 
first you multipy, then combine terms
 
so multiplying we get
 
-3x - 3 = 2x - 16 +3
 
Now combine get like terms on the same side of the equation
 
-3x - 2x = 3 - 16 + 3   (got here by adding 3 to both sides and subtracting -2x from both sides)
 
Combine
 
-5x = -10
 
Divide both sides by -5
 
x = 2   This is the solution
Hi Abby
–3(x + 1) = 2(x – 8) + 3
Let's distribute the -3 on the left side, and the 2 on the right side...
-3x-3=2x-16+3
-3x-3=2x-13
Add 3 to both sides...
-3x-3+3=2x-13+3
-3x=2x-10
Subtract 2x from both sides...
-3x-2x=2x-10-2x
-5x=-10
Divide both sides by -5...
(-5x)/-5=-10/-5
x=2
 
Let's check our work...
–3(x + 1) = 2(x – 8) + 3
–3(2 + 1) = 2(2 – 8) + 3
-3(3)=2(-6)+3
-9=-12+3
-9=-9